Assessing digital competencies: A self-evaluation approach for university students' academic success - Arco, Isabel del; Flores-Alarcia, Òscar; Balladares, Jorge; Quintero, Gina (Journal of Education and e-Learning Research, 2025)
University students must be equipped with key digital competencies in Education 4.0, where connectivity, technological fluency, and digital literacy are essential for academic and professional development. This study analyzes the self-perceived digital competencies of university students enrolled in education degrees across seven universities in Spain and Latin America. Data were collected through an online survey comprising Likert-scale items assessing five core areas of digital competence aligned with the DigComp framework: information management, communication, content creation, digital safety, and problem-solving using a quantitative and descriptive methodology. The results show that students feel most competent using digital technologies to communicate, share information and search for and manage data. However, significant weaknesses were identified in areas, such as digital content creation, pro-gaming, and solving technical problems as well as managing digital safety and copyright issues. Gender and age differences were statistically significant although with small effect sizes. These findings highlight the need to enhance training programs in higher education, especially in underdeveloped areas of digital competence to better prepare future teachers. This research contributes to the growing knowledge on digital self-assessment and underscores the importance of integrating comprehensive digital literacy into teacher education curricula.